2016
DOI: 10.1038/npjpcrm.2015.80
|View full text |Cite
|
Sign up to set email alerts
|

Help-seeking and antibiotic prescribing for acute cough in a Chinese primary care population: a prospective multicentre observational study

Abstract: Acute cough is a common reason to prescribe antibiotics in primary care. This study aimed to explore help-seeking and antibiotic prescribing for acute cough in Chinese primary care population. This is a prospective multicentre observational study that included adults presenting with acute cough. Clinicians recorded patients’ presenting symptoms, examination findings and medication prescription. Patients completed symptom diaries for up to 28 days by charting their symptom severity and recovery. Adjusted binary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 17 publications
1
22
1
Order By: Relevance
“…GPs and other primary care doctors are more likely to prescribe antibiotics to patients who expect them or whom they believe expect them [ 36 , 40 , 41 , 43 , 44 , 46 – 56 ]. This experience is replicated with other non-medical PCPs [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…GPs and other primary care doctors are more likely to prescribe antibiotics to patients who expect them or whom they believe expect them [ 36 , 40 , 41 , 43 , 44 , 46 – 56 ]. This experience is replicated with other non-medical PCPs [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Measurement of patient expectation for antibiotic treatment for ARTI varies from 74% [ 58 , 59 ] to 10% [ 41 ], with many measurements in between [ 60 64 ]. The study showing 10% patient expectation for antibiotics was conducted in China among patients presenting with ARTI symptoms and found that concern about illness severity and obtaining symptomatic treatment were the main reasons for consulting with ARTI rather than obtaining antibiotics [ 41 ]. The two studies showing the highest patient expectation rates were both studies of parents’ attitudes to antibiotic prescribing for their children who were not sick at the time, and were based in Greece and Palestine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prescribing clinicians may perceive these as risk factors for more severe or longer-lasting illness, or secondary infection [1820], and may be more likely to prescribe antibiotics to these patients [6, 21]. …”
Section: Discussionmentioning
confidence: 99%